Concurrent Infection of Cestodes with Trichomoniasis in Domestic and Wild Columbides Birds in Babylon Province: Hayder M. Al-Rammahi1 ; Mohammad H. AL-Hasnawy1 and Athmar K. Abbas2 - Abbas, Athmar K. (The Iraqi Journal of Veterinary Medicine, 2013)
The research was carried out in Babylon province on 138 domestic and wild columbide birds were collected during the period from April to June 2012. Fresh saline smears samples (wet mount) were taken from mucosa of buccal cavity, pharynx ,esophagus and crop of each bird, then examined by wet mount looking for Trichomoniasis, then the intestine opened longitudinally examined looking for helminthes which examined grossly and after fixative staining with carmine stain for identification. The results of wet mount for Trichomonus technique revealed that the total rate of infection was 43(31.5%). Asignificant differences were recorded in the rates of infection regarding the species of birds. The highest rate of infection was recorded with Trichomonus gallinae, in wood pigeon 16 (53.33%) followed by Rock pigeon, Domestic pigeon, Collared dove and palm dove 12(40%), 9 (30%), 4(13.34%) and 2(11.12 %) respectively. The results revealed that the total rate of infection was 80 (57.97%), with cestodes parasite. Asignificant differences regarding the type of the birds, the highest prevalence was recorded in wood pigeons 27 (90%) followed by rock pigeon, collared dove and domestic pigeons in prevalence rate 25 (83.34%), 12 (40%) and16 (26.67%) respectively, while no cestods recorded in palm dove. Asignificant differences regarding the type of cestodes parasite. Out of 123 collected cestodes, 79 (64.23%) were geuns Raillietina (18.69%) were geuns Aporina, and (17.07%) were geuns Cotugnia